2021
DOI: 10.1038/s41385-021-00379-6
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary vaccination with delta-inulin adjuvant stimulates non-polarised chemotactic signalling and diverse cellular interaction

Abstract: There is an urgent need for novel vaccination strategies to combat respiratory pathogens. Mucosal vaccine delivery is an attractive option as it directly targets the site of infection; however, preclinical development has been hindered by a lack of suitable mucosal adjuvants and a limited understanding of their immune effects in the lung environment. Herein, we define the early immune events following the intrapulmonary delivery of a vaccine incorporating the adjuvant delta-inulin. Analysis of the early inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Thus delta-inulin's potential as an adjuvant for lung vaccinations is again supported by this preclinical study. 63 Human clinical trials using delta inulin as adjuvant against hepatitis B 64 and influenza vaccine 65 have also been reported to be successful in providing safety, immunogenicity, and tolerability for even infants and children between ages 6 months and 9 years, supporting the objective of this review. Apart from delta inulin, another crystalline type of inulin called the gamma inulin (γ-inulin) has also shown adjuvant activity.…”
Section: Inulinmentioning
confidence: 54%
“…Thus delta-inulin's potential as an adjuvant for lung vaccinations is again supported by this preclinical study. 63 Human clinical trials using delta inulin as adjuvant against hepatitis B 64 and influenza vaccine 65 have also been reported to be successful in providing safety, immunogenicity, and tolerability for even infants and children between ages 6 months and 9 years, supporting the objective of this review. Apart from delta inulin, another crystalline type of inulin called the gamma inulin (γ-inulin) has also shown adjuvant activity.…”
Section: Inulinmentioning
confidence: 54%
“…Lungs and lymph nodes were processed as described previously 17 . Intravascular staining was performed by the intravascular injection of 15 µg/mL CD45-biotin (clone 30-F11, BioLegend, CA, USA) three minutes before euthanasia.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously demonstrated that intrapulmonary vaccination with a subunit tuberculosis vaccine formulated with the particulate polysaccharide adjuvant Advax TM generates robust resident memory T cells (TRMs) in the lungs along with systemic antibody responses 16 . The early pulmonary immune response to this vaccine is characterized by a broad chemotactic response that does not result in lasting inflammation 17 . While intranasal administration models are widely used, we selected the intrapulmonary route due to several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Given this is thought to be an immune correlate of protection against M. abscessus , these adjuvants may be useful components of an M. abscessus vaccine. Appropriate selection of adjuvant (such as one with a minimal inflammatory profile) may also facilitate non-parenteral vaccine administration, such as vaccine delivery directly to the respiratory mucosa ( Ferrell et al, 2021 ). There is renewed interest in pulmonary vaccination for TB, whereby delivery of the vaccine directly to the lung induces tissue-resident populations capable of rapid response to M. tb ( Counoupas et al, 2020 ).…”
Section: Toward the Development Of A Mycobacterium Abscessu...mentioning
confidence: 99%